Effect of the Sulfated Zirconia Nanostructure Characteristics on Physicochemical and Electrochemical Properties of SPEEK Nanocomposite Membranes for PEM Fuel Cell Applications. Issue 5 (15th March 2018) - Mossayebi, Zahra; Parnian, Mohammad Javad; Rowshanzamir, Soosan
Abstract: This study expresses that the characteristics of sulfated zirconia (SZ) nanostructure in sulfonated poly(ether ether ketone) (SPEEK)‐based membranes is the key to optimize their properties for fuel cell applications. Two types of SZ treating in different thermal conditions are produced by precipitation and analyzed by X‐ray diffraction, thermogravimetric analysis, Fourier transform infrared spectroscopy, energy‐dispersive X‐ray analysis, and transmission electron microscopy. Sulfate concentration on both types of SZ is changing from 0.54 to 1.45 wt% and thus the SZ samples differ in particle size and sulfate content. The nanocomposite membranes are prepared by incorporating 6 wt% of SZ samples into SPEEK matrix in casting procedure followed by performing electrochemical characterizations and impedance spectroscopy. Moreover, morphology, mechanical, and chemical stability of the membranes are investigated by field emission scanning electron microscopy, stress–strain, and ex situ Fenton's tests. The incorporation of SZ sample having more surface sulfate groups in the SPEEK matrix results in not only excessive oxidative stability and tensile strength but also more acidic sites for ion transport, promoting conductivity. Furthermore, both types of nanocomposite membranes show improved ionic conductivity and water affinity with a lower tendency to swell rather than the plain SPEEK membrane. It is proved that desired consequences of doping SZ into SPEEK matrix can be intensified by changing the physicochemical properties of sulfated zirconia nanoparticles. Abstract : A comparison between two types of sulfated zirconia (SZ) treating in different thermal conditions for the purpose of synthesis of sulfonated poly(ether ether ketone) (SPEEK)‐based nanocomposite membranes is made. Since the incorporation of SZ into SPEEK provides additional acidic sites, SZ sample having more sulfate groups represents higher conductivity.